A cognitive behavioural theory of anorexia nervosa. - Fairburn, C; Shafran, R; Cooper, Z (1999)
A cognitive behavioural theory of the maintenance of anorexia nervosa is proposed. It is argued that an extreme need to control eating is the central feature of the disorder, and that in Western societies a tendency to judge self-worth in terms of shape and weight is superimposed on this need for self-control. The theory represents a synthesis and extension of existing accounts. It is 'new', not so much because of its content, but because of its exclusive focus on maintenance, its organisational structure and its level of specification. It is suggested that the theory has important implications for treatment.